2014
DOI: 10.1111/gcb.12755
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic pollen season variations in the past two decades under changing climate in the United States

Abstract: Many diseases are linked with climate trends and variations. In particular, climate change is expected to alter the spatiotemporal dynamics of allergenic airborne pollen and potentially increase occurrence of allergic airway disease. Understanding the spatiotemporal patterns of changes in pollen season timing and levels is thus important in assessing climate impacts on aerobiology and allergy caused by allergenic airborne pollen. Here we describe the spatiotemporal patterns of changes in the seasonal timing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 47 publications
3
94
0
4
Order By: Relevance
“…For example, D'Amato and Cecchi (2008) have shown that low humidity favors the release, dispersion, and transport of pollen with a consequent rise in allergic effects. In contrast, a 28 build-up in atmospheric moisture, often leading to thunderstorm formation, may cause short-term increases in asthma epidemics through the release of allergens caused by pollen grain rupture via osmotic shock (D'Amato et al, 2013;Zhang et al, 2015).…”
Section: Air Qualitymentioning
confidence: 99%
“…For example, D'Amato and Cecchi (2008) have shown that low humidity favors the release, dispersion, and transport of pollen with a consequent rise in allergic effects. In contrast, a 28 build-up in atmospheric moisture, often leading to thunderstorm formation, may cause short-term increases in asthma epidemics through the release of allergens caused by pollen grain rupture via osmotic shock (D'Amato et al, 2013;Zhang et al, 2015).…”
Section: Air Qualitymentioning
confidence: 99%
“…As confirmed by the results of numerous studies, climate change causes changes in the growth cycle of plants. The results of phenological observations, in particular flowering observations (Chmielewski & Rötzer, 2001;Primack et al, 2004;Czernecki & Jabłońska, 2016), but also aerobiological observations allow us to determine precisely the beginning and end of pollen release in plants (Frei & Gassner, 2008;Puc et al, 2015;Zhang et al, 2015). The results of these observations are the strongest biological signal of the existence of such changes.…”
Section: Dabrowska Et Almentioning
confidence: 99%
“…Zhang et al, 2014). Climatic changes in large-scale pollen distributions are mostly absent from scientific literature, though mul-4106 M. C. Wozniak and A. L. Steiner: A prognostic pollen emissions model for climate models (PECM1.0) tiple studies on phenological changes in the pollen season have been published (Ziska, 2016;Yue et al, 2015;Y. Zhang et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%